Multiple bHLH/MYB-based protein complexes regulate proanthocyanidin biosynthesis in the herbage of Lotus spp - Escaray, Francisco José (2024)
The environmental impact and health of ruminants fed with forage legumes depend on the herbage's concentration and structure of proanthocyanidins (PAs). Unfortunately, the primary forage legumes (alfalfa and clover) do not contain substantial levels of PAs. No signifcant progress has been made to induce PAs to agronomically valuable levels in their edible organs by biotechnological approaches thus far. Building this trait requires a profound knowledge of PA regulators and their interplay in species naturally committed to accumulating these metabolites in the target organs. Against this background, we compared the shoot transcriptomes of two inter-fertile Lotus species, namely Lotus tenuis and Lotus corniculatus, polymorphic for this trait, to search for diferentially expressed MYB and bHLH genes. We then tested the expression of the above-reported regulators in L. tenuis x L. corniculatus interspecifc hybrids, several Lotus spp., and diferent L. corniculatus organs with contrasting PA levels. We identifed a novel MYB activator and MYB-bHLH-based complexes that, when expressed in Nicotiana benthamiana, trans-activated the promoters of L. corniculatus anthocyanidin reductase and leucoanthocyanidin reductase 1 genes. The last are the two critical structural genes for the biosynthesis of PAs in Lotus spp. Competition between MYB activators for the transactivation of these promoters also emerged. Overall, by employing Lotus as a model genus, we refned the transcriptional network underlying PA biosynthesis in the herbage of legumes. These fndings are crucial to engineering this trait in pasture legumes.